Prevalence and risk factors of human papilloma virus infection among women living with HIV, Egypt, a cross sectional study - Mona Ashry; Shaimaa Shawky; Zeinab Mounir; Fawzy Fathy; Heba Elsayed; Walid Kamal; Mohamed Hassany (BMC, 2024)
Abstract Background HPV is considered the most common sexually transmitted infection. It is responsible of 70% of cervical cancers worldwide. HIV infection is associated with increased rates of HPV infection. Women Living With HIV (WLWH) are 6 times at greater risk of developing cervical cancer. The current study aimed to estimate prevalence and identify genotypes of HPV infection among WLWH in Egypt compared to women with negative HIV status and determine associated risk factors. Methods The study conducted among 251 WLWH and 268 women with negative HIV status enrolled from gynecological clinics in primary health care centers from nine Egyptian governorates. Data was collected from participants using a structured interview questionnaire and cervical samples were collected for HPV DNA detection and genotyping. Results The overall prevalence of HPV infection was 13.5%, 3.4% among women with HIV negative status and 24.4% among WLWH. HR-HPVs other than genotype 16 and 18 were isolated from 71% of infected women. Woman's age, age at first marriage, number of lifetime marriages and drug addiction are significant predictors for HPV infection (odds 0.96, 0.91, 2.06, 2.01 respectively). Conclusion HPV infection is more prevalent among WLWH. Infection with HR-HPV other than genotype 16 and 18 was the most prevalent among infected women in both groups. Young age, early life sexual activity, having more than one sexual partner during the life time, and drug addiction are independent predictors for HPV infection. Having a husband who has had other sexual partners is significantly associated with infection.